Optimization of Protein Quality Assay in Normal, opaque-2, and Quality Protein Maize - Kaur, Charanjeet; Singh, Alla; Sethi, Mehak; Devi, Veena; Chaudhary, Dharam Paul; Phagna, Ramesh Kumar; Langyan, Sapna; Bhushan, Bharat; Rakshit, Sujay (Frontiers in Sustainable Food Systems, 2022)
The development of quality protein maize (QPM) was considered a significant leap toward improvement in the nutritional status of rural masses in developing countries. The nutritional quality of QPM is attributed to the higher concentration of essential amino acids, particularly lysine and tryptophan, in its kernel endosperm. However, the similarity in the grains of QPM and normal maize necessitates the development of a standard protocol to assess the protein quality of maize. The present study aimed at improving the protocol of protein quality assessment in QPM. For this purpose, endosperm defatting and protein estimation procedures were restandardized and optimized with respect to the protocol duration and its amenability for high-throughput analysis. Unlike normal maize, QPM and opaque-2 mutants were completely defatted within a 48 h period. It was observed that the tryptophan content, calculated at each defatting interval, increased in the samples defatted for a longer duration. No significant differences were observed in the tryptophan content analyzed in the samples defatted for 48 and 72 h. Moreover, the endosperm protein estimated by using the Bradford method with certain modifications strongly correlated with the micro-Kjeldahl method (r = 0.9). Relative to the micro-Kjeldahl method, the Bradford method was found to be precise, rapid, and hazard-free. The present findings enable a testing protocol of reduced time duration that can be used in resource-poor settings for the determination of a protein quality assay in QPM. Overall, the present study effectively helped in reducing the defatting time by 24 h and protein estimation by 3 h as compared to the already established International Maize and Wheat Improvement Center protocol. This is expected to enable the aggregation of high-protein-quality maize to facilitate its commercialization.